Foliar Fertilizer and Pesticide Methomyl 25% in Tea Plantation after Infested by Pest. (1) Effect of Productivity Increasing and Yield Components - haq, muthia syafika; Fauziah, Fani; Karyudi, Karyudi (Research Institute for Tea and Cinchona, 2015)
The experiment of effect of Foliar Fertilizer (N& ZnSo4) and pesticide compatibility with Methomyl 25% compound to increasing Tea Productivity (Camellia sinensis) has been conducted in Research Institute for Tea and Chincona experimental plantation1350 m above sea level and andysol type soil. The experiment started from November 2013 â Februari 2014 Â in produced tea area with 1.080 plant population. Material plantswere GMB 4 clones with second pruning year and 12 days plucking interval. The experiment was arranged on randomized block design with 9 treatments and 3 replicate. Foliar fertilizer and pesticide combination which has been examinedÂ were Â (1) Methomyl 25% (control), (2) Methomyl 25% + Zn 1%, (3) Methomyl 25% + Zn 2%, (4) Methomyl 25% + N 1%, (5) Methomyl 25% + N 2%, (6) Methomyl 25% + N 1% + Zn 1%, (7) Methomyl 25% + N 1% + Zn 2%, (8) Methomyl25% + N 2% + Zn 1%and (9) Methomyl25% + N 2% + Zn 2. Spraying application done every after plucking. The resultsÂ showed that skiffing treatment can control the tea plantation that infested by pest and stimulate the new bud growth. The resultsÂ also showed that productivity increased significantly up to37, 48 % (2.781 gr/40 plants) when the plants were treated with Methomyl + N 1% + Zn 2%.But,the increased production is accompanied by an increase of banjhi because plant still using their nutrition to recovering after pest infested. The weight of pecco which grown from theÂ lateral buds is relatively small because of skiffing. Bud growth rate after given treatment was obtained only 3-4 cm/ 6 days caused by lack of light intensity at the time of reserached